Perception of Youth on Reproductive Health in Boarding Boarding La Tansa in 2021 - Elsya Zaina Elidzar; Himmatul Ulya; Mega Rizki Utami; Munaya Fauziah (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2021)
The problems of health reproduction adolescents in Indonesia caused not optimal commitment and support of the government in the form of a policy that is set on the education of sexual and reproduction for adolescents in order of family, community, and school. To continue the struggle of the nation, it is hoped that youth have ethics and morals that are responsible for the good.This study aims to determine Adolescent Perceptions of Reproductive Health in students at the La Tansa Islamic Boarding School. The research method used is qualitative research with in-depth interviews. Informants will be conducted in-depth interviews are three informants students teenage daughter at Pondok Pesantren La Tansa. The results of the study showed that the discussion about health reproduction is not a thing taboo to talk about. In the handling of all the problems of health reproduction usually with medication to the doctor or even just be left alone (in the case of vaginal discharge ), but seldom of them that experience interference health reproduction. A sense of shame and is still considered taboo became one of the factors that did not perform the treatment when it occurs the problem. Many once the benefits that will be obtained when held counseling about health reproduction, but the media are used also should be expected to make the students understand to be things about the health of reproduction it alone. To conduct counseling health cottage boarding they rarely conduct outreach on the topic of this, in addition to the situation of a pandemic covid-19 now makes counseling difficult to do because be no crowd. Based on the results of the analysis and discussion of the research is that the perception of adolescents about health reproduction in Pondok Pesantren La Tansa year 2021 is still low because of lack of knowledge of teen-related health reproduction in pond ok boarding it.